Forecasting techniques based on the use of time series models for forecasting expenditures on social protection and social security - Zarudnyi, O.; Koval, R. (Проблеми керування та інформатики, 2024)
The aim of the paper is to consider modern methods of analyzing and forecasting time series and propose their application to determine the need for spending on social protection and social security. Мета роботи — розглянути сучасні методи аналізу та прогнозування часових рядів та запропонувати застосування цих методів для визначення потреби у видатках на соціальний захист та соціальне забезпечення.